The role of ultrasonography in the diagnosis of painful shoulder syndrome in rheumatoid arthritis - Samia Abd El Hamid Abd El Megid; Mohammed T Abdel-Hak; Marwa M.A Abd El Rahim; Ibtesam H Abdel-Whab Hassan (Wolters Kluwer Medknow Publications, 2018)
Aim of the work To identify the role of ultrasonography in diagnosis of painful shoulder syndrome in rheumatoid arthritis (RA). Patients and methods A total of 45 patients with RA who fulfilled the ACR/EULAR 2010 criteria for RA were included, involving 65 shoulders. There were seven male and 38 female patients, and their mean age was 48.02±15.41 years. Their mean disease duration was 15.5±11.25 years. They were subjected to full history taking, thorough clinical examination, laboratory investigations, plain radiography, and shoulder ultrasonography. Results The 65 RA shoulders were divided according to the disease activity score 28 (DAS28) into group A (with high DAS28), which included 15 (23%) shoulder joints, and group B (with moderate DAS28), which included 50 (77%) shoulder joints. Ultrasound findings of groups A and B revealed bicipital tenosynovitis in 47 and 22%, rotator cuff (RC) tendinopathy in 66.7 and 24%, humeral head erosions in 80 and 48%, effusion in 66.7 and 18%, subacromial/subdeltoid (SA/SD) bursitis in 66.7 and 28%, and positive power Doppler signals (PDS) in 60 and 14%, respectively. There was a highly significant difference in effusion and a significant difference in RC tendinopathy and SA/SD bursitis between both groups. There was a significant to highly significant difference in SA/SD bursitis, RC tendinopathy, and bicipital tenosynovitis between patients with positive and negative PDS. Conclusion Ultrasonography is a useful tool in the diagnosis of shoulder pain in RA that can distinguish between various causes, helping in proper decision making regarding the treatment strategy. Bicipital tenosynovitis, SA/SD bursitis, glenohumeral joint effusion, humeral head erosions, and positive PDS were significant predictors of inflammatory nature of the painful shoulder syndrome.